PEMANFAATAN BAHAN PENGGUMPAL ORGANIK SEBAGAI KOAGULAN LATEKS - Rizki Riyan Nopri; Ika Ucha Pradifta Rangkuti; Pada Mulia Raja (Jurnal Agro Fabrica, 2021)
Latex is a white, milky liquid that comes out of injured plants from the Hevea brasiliensi plant. Heveabrasiliensi latex can be processed into rubber because it has good properties which contain rubber particlesin the form of poly isopropene hydrocarbons which are the main components of rubber. In this study, latexcoagulation used an organic coagulant as a latex coagulant, namely extract from pineapple fruit and liquidsmoke from rubber wood, oil palm midrib, coconut shell. The results of coagulation were measured by thequality of dry rubber content (KKK) and PRI. Supported by secondary data, namely literature taken fromjournals and browsing on the internet. The results showed that the best coagulant material was produced bypineapple extract 80%, liquid smoke of coconut shell with a pH of 4.1, liquid smoke of palm fronds with a pHof 3.2, and liquid smoke of rubber wood with a pH of 2.6.